The role of cytochromes p450 and aldo-keto reductases in prognosis of breast carcinoma patients - Hlaváč, Viktor; Brynychová, Veronika; Václavíková, Radka; Ehrlichová, Marie; Vrána, David; Pecha, Václav; Trnková, Markéta; Kodet, Roman; Mrhalová, Marcela; Kubáčková, Kateřina; Gatěk, Jiří; Vážan, Petr; et al. (Medicine, 2014)
Metabolism of anticancer drugs affects their antitumor effects. This study has investigated the associations of gene expression of enzymes metabolizing anticancer drugs with therapy response and survival of breast carcinoma patients. Gene expression of 13 aldo-keto reductases (AKRs), carbonyl reductase 1, and 10 cytochromes P450 (CYPs) was assessed using quantitative real-time polymerase chain reaction in tumors and paired adjacent nonneoplastic tissues from 68 posttreatment breast carcinoma patients. Eleven candidate genes were then evaluated in an independent series of 50 pretreatment patients. Protein expression of the most significant genes was confirmed by immunoblotting. AKR1A1 was significantly overexpressed and AKR1C1-4, KCNAB1, CYP2C19, CYP3A4, and CYP3A5 downregulated in tumors compared with control nonneoplastic tissues after correction for multiple testing. Significant association of CYP2B6 transcript levels in tumors with expression of hormonal receptors was found in the posttreatment set and replicated in the pretreatment set of patients. Significantly higher intratumoral levels of AKR1C1, AKR1C2, or CYP2W1 were found in responders to neoadjuvant chemotherapy compared with nonresponders. Patients with high AKR7A3 or CYP2B6 levels in the pretreatment set had significantly longer disease-free survival than patients with low levels. Protein products of AKR1C1, AKR1C2, AKR7A3, CYP3A4, and carbonyl reductase (CBR1) were found in tumors and those of AKR1C1, AKR7A3, and CBR1 correlated with their transcript levels. Small interfering RNA-directed knockdown of AKR1C2 or vector-mediated upregulation of CYP3A4 in MDA-MB-231 model cell line had no effect on cell proliferation after paclitaxel treatment in vitro. Prognostic and predictive roles of drug-metabolizing enzymes strikingly differ between posttreatment and pretreatment breast carcinoma patients. Mechanisms of action of AKR1C2, AKR7A3, CYP2B6, CYP3A4, and CBR1 should continue to be further followed in breast carcinoma patients and models.
Keywords: systém (enzymů) cytochromů P-450; imunoblotting; regulace genové exprese u nádorů; Humans; Tumor Cells, Cultured; Aldo-Keto Reductases; Female; aldehydreduktasa; aldo-keto reduktasy; lidé; proliferace buněk; Aldehyde Reductase; nádorové buňky kultivované; RNA, Neoplasm; Cytochrome P-450 Enzyme System; Breast Neoplasms; RNA nádorová; ženské pohlaví; Flow Cytometry; Cell Proliferation; prognóza; nádory prsu; Real-Time Polymerase Chain Reaction; Immunoblotting; průtoková cytometrie; Prognosis; prospektivní studie; Gene Expression Regulation, Neoplastic; kvantitativní polymerázová řetězová reakce; Prospective Studies